Les corridors industriels en Inde - Philippe Cadène; Yves-Marie Rault (EchoGéo)
Since the early 2000s, the Indian State has engaged into a territorial development policy that supports investments along corridors with modernized transport infrastructures and adapted areas to accommodate businesses. Five « industrial or economic corridors » have been formally identified by the government, connecting the country's largest cities. The analysis of business locations shows that, in a context of strong and sustained growth, the country’s productive capital is concentrating in the main cities and along corridors, shaping large regions capturing investments and industrial activities. The location of companies is determined by a set of complex factors. Their logics are distinct from the State development strategies and are framed in a governance which strengthens the role of regional public authorities and private actors in the spatial structuration of India.